Development of marketing strategies in system-reflexive marketing - Dligach, Andrii (Technology audit and production reserves, 2017)
The author introduces the concept of system-reflexive strategic marketing management, represents a new paradigm of marketing and strategic management and generalizes the stages of their evolutionary development. System-reflexive approach in the formation of marketing strategies allows proactively manage the development of market interaction; determines the subjective position of the manager, which makes it possible to realize his interests by implementing an appropriate marketing strategy; increases business competitiveness and accelerates the diffusion of innovation. The proposed integrated SRSMM system is based on a program management form in which interests, goals, strategies, and the strategic plan are not definite and static in the planning horizon, and the management activity itself presupposes constant clarification of interests, goals, strategies and plans. In the course of the research it is revealed that for the introduction of the program form of system-reflexive strategic marketing management, a three-cycle management model is required as a set of methods, forms and tools for coordinating stakeholder interests at three levels: (1) objectifying the manager's interest in the management object, as well as actualizing interest in relation to other interests of the manager, the result is the prevailing view of the management object and the direction of its transformation (objectified interest), related for manager with the expected benefits from the transformation; (2) aligning the interests of internal stakeholders, including the reflexive marketing manager; (3) formation of a strategy in the process of coordinating the interests of external stakeholders, which, unlike existing approaches, allowed to reflect the subject approach in the formation of entrepreneurial strategies and to develop a mechanism for managing the alignment of stakeholder interests in the process of forming a marketing strategy. The use of system-reflexive marketing in the activities of the enterprise makes it possible to constructively resolve internal and external conflicts, to form a strategic vision and corporate strategy, to help the subjects of management to determine the object of management and their own interests in relation to it; increases the efficiency of activities. In turn, this contributes to the development of entrepreneurship in Ukraine and to increase the competitiveness of domestic enterprises in a globalized market environment.